Ethiopian isolates of nematophagus fungi have effectively killed Haemonchus contortus infective larvae in vitro - Tadesa Tilahun; Solomon Shiferaw; Hika Waktole; Gezahegne Mamo; Muluken Tekle; Getachew Terefe (BMC Veterinary Research)
Abstract Introduction The effectiveness of anthelmintics in controlling gastrointestinal parasitism in livestock is increasingly threatened by the emergence of drug resistance. To address this issue, biological control methods have been proposed as potential alternatives. This research aimed to evaluate the efficacy of nematophagous fungi isolated from soil samples against Haemonchus contortus infective larvae. Material and methods Soil samples were collected from Ambo and Hawasa, representing the central and southern regions of Ethiopia, respectively. The fungi were cultured on 2% water agar using the soil sprinkling technique. Fungal identification was conducted based on conidial morphology and adhesive networking. Results Arthrobotrys oligospora (AO), Arthrobotrys conoides (AC) and Monacrosporium species (MS) were isolated from the soil samples. In vitro tests on 2% water agar demonstrated that the trapping and killing of H. contortus L3 larvae began within 48 h of exposure. From second to 4th day of observation, significant difference in the number of dead larvae were observed between the untreated control (UTC) and treatment plates (P < 0.0001); mortality being 99.77 ± 0.38%, 96.74 ± 3.15%, 89.92 ± 4.31 and 9.92 ± 3.45% for AC, AO, MS and UTC groups. Monacrosporium species was less effective compared to both AC and AO (P > 0.05). When accounting for natural mortality (control), the contributions to larval deaths attributed to AC, AO, and MS were 90%, 89.7%, and 88.9%, respectively. The introduction of AC and AO spores to H. contortus egg-positive feces significantly decreased the number of live larvae recovered compared to the UTC (P < 0.0001) with percentage recovery of 1.6 ± 0.31%, 11.09 ± 1.41% and 49 ± 4.75% respectively. Sheep treated with conidia of AC and AO expelled varying numbers of conidia in the first 24 h post-treatment, with AO reducing larval development by 80–86% and AC by 84–87% when the natural reduction in the UTC plates is taken into account. Conclusion This study for the first time has demonstrated the in vitro efficacy of nematode trapping fungal isolated from Ethiopian soil. Further research is needed to evaluate their performance on pasture.